Enhancing Mufradat Memorization Through Word Square Learning Media: A Study of Class VII Students at MTs Muhammadiyah Pinrang - Nur Madinah; Nur Fadilah Fadilah Amin; Abd. Rahman (Prodi Pendidikan Bahasa Arab, Universitas Muhammadiyah Tangerang, 2025)
This study explores the application of Word Square learning media to enhance the memorization of Arabic mufradat (vocabulary) among seventh-grade students at MTs Muhammadiyah Pinrang. The research addresses the challenge of low vocabulary retention, a critical issue in Arabic language learning, and aims to determine whether the interactive, game-based Word Square method can enhance student engagement and memorization.A Classroom Action Research (CAR) design was employed, conducted in two cycles. Data were collected through observations, pre- and post-tests, and documentation, and analyzed using both qualitative and quantitative methods. In the first cycle, while student engagement increased, only a modest improvement in vocabulary retention was observed. Adjustments were made in the second cycle, including simplifying the puzzles and encouraging collaborative learning, which led to a significant increase in student performance.The results showed that Word Square is an effective tool for improving vocabulary retention, with most students achieving